At the same time ...: the expression of simultaneity in learner varieties - Mertins, Barbara (Studies on language acquisition, 2008)
Biographical note: Barbara Schmiedtová is Researcher at the Max-Planck-Institute for Psycholinguistics, Nijmegen, The Netherlands.